Vegetable oils utilization in the recipes of meat pates - Topchiy, Oksana; Kotlyar, Eugene (My University, 2013)
The main problem is the creation of products with high nutritional and biological value. Also quite common problems such as lack of fiber mikronutriyentyiv (vitamins, minerals, fatty acids, etc.), unbalanced nutrition in Ukraine. Abnormalities in the structure of food involves the need for functional foods, including functional meat products.
Keywords: meat; pates; oils; recipes; м'ясо; паштети; олії; рецептури; мясо; паштеты; масла; рецептуры; кафедра технології м’яса і м’ясних продуктів